A Cross Sectional Survey-Based Study to Investigate the Availability and Utilisation of Home Nutrition Support in Saudi Arabia - Zaher S; Ajabnoor SM (Journal of Multidisciplinary Healthcare, 2023)
Sara Zaher,1,2 Sarah M Ajabnoor2,3 1Clinical Nutrition Department, Faculty of Applied Medical Sciences, Taibah University, Madinah, Saudi Arabia; 2National Nutrition Committee (NNC), Saudi Food and Drug Authority (Saudi FDA), Riyadh, Saudi Arabia; 3Clinical Nutrition Department, Faculty of Applied Medical Sciences, King Abdulaziz University, Jeddah, Saudi ArabiaCorrespondence: Sara Zaher, Clinical Nutrition Department, Faculty of Applied Medical Sciences, Taibah University, P.O. Box 344, Madinah, 42353, Saudi Arabia, Email Sz332@cam.ac.uk; szaher@taibahu.edu.saBackground and Aims: Many patients require long-term nutrition support, typically in the form of home nutrition support (HNS). The availability and utilisation of HNS in Saudi Arabia is currently unknown; therefore, this study was conducted to assess the availability of HNS in Saudi hospitals and to explore factors associated with the availability of HNS in different healthcare facilities in Saudi Arabia.Methods: A cross-sectional study was conducted among physicians, dietitians, and pharmacists working in Saudi Arabia with regular practice in nutrition support. Data was collected through self-administered web-based survey, which was distributed via social-media platforms.Results: A total of 114 responses were received from healthcare providers involved in nutrition support across Saudi Arabia. Of the respondents, 55 (48.2%) indicated that nutrition support services were available at their facility. Regression analysis showed that other regions in Saudi Arabia had lower odds of having HNS compared with the Western region (OR=0.01; 95% CI=0.01– 0.69). The university and specialised hospitals had lower odds of having HNS compared with Ministry of Health hospitals (OR=0.11; 95% CI=0.02− 0.71, OR=0.11; 95% CI=0.02− 0.56, respectively). Hospitals with capacities of 100– 250 beds and 251– 500 had higher odds of having HNS than smaller hospitals (OR=13.17; 95% CI=1.09– 159.5, OR=3.11; 95% CI=2.04– 248.77, respectively).Conclusion: There is lack of published reports from hospitals with implemented HNS. Therefore, it is difficult to assess the current situation of HNS programmes. Future national studies focusing on HNS are warranted as there is a rising international trend in the number of patients requiring HNS.Keywords: home enteral nutrition, home parenteral nutrition, home nutrition support